Conservation actions and ecological context: optimizing coral reef local management in the Dominican Republic - Camilo Cortés-Useche; Edwin A. Hernández-Delgado; Johanna Calle-Triviño; Rita Sellares Blasco; Victor Galván; Jesús E. Arias-González (PeerJ, 2021)
Over the past few decades, coral reef ecosystems have been lost at accelerated rates as a result of global climate change and local stressors. Local management schemes can help improve the condition of coral reefs by enhancing their ecosystem recovery capacity. Caribbean conservation efforts include mitigation of local anthropogenic stressors, and integrating social participation. Here, we analyzed the case of the Bayahibe reefs in the Southeastern (SE) Dominican Republic to identify conservation actions and illustrate a conceptual example of local seascape management. We assessed reef health indicators from 2011 to 2016. Overall, our results show increases in total fish biomass, in both commercial and herbivorous fishes. Mean live coral cover was 31% and fleshy macroalgae was 23% after multiple disturbances such as Hurricanes Sandy and Isaac (2012), Mathew (2016) and heat stress presented in the study area in 2015. We also described actions taken by stakeholders and government institutions, including the implementation of a policy declaring an area of 869,000 ha as a marine protected area (MPA), enhanced water quality treatment, local restrictions to vessel traffic, enforcement of fishing regulations, and the removal of invasive lionfish (Pterois spp.). In addition, a restoration program for the threatened staghorn coral (Acropora cervicornis) was established in 2011, and currently has eight coral nurseries and six outplanting sites. Considering the biology and ecology of these reefs, we observed good results for these indicators (live coral cover, fish biomass, and water quality) in contrast with severely degraded Caribbean reefs, suggesting that optimizing local management may be a useful example for improving reef condition. Our results provide an overview of trends in reef condition in the SE Dominican Republic and could support current strategies to better protect reefs in the region. Given that Caribbean coral reefs face extreme challenges from global climate change, management measures may improve reef conditions across the region but stronger policy processes and increased scientific knowledge are needed for the successful management of coral reefs.